IMPROVEMENT IN VISUAL ACUITY SIX MONTHS AFTER PENETRATING KERATOPLASTY IN PATIENTS OF KERATOCONUS - Ansari, Muhammad Sufyan; Zulfiqar, Nabila; Nafees, Khurram; Shaheen, Manzra (Journal of Ayub Medical College Abbottabad, 2021)
Background: Keratoconus (KC) is a bilateral, asymmetric, corneal disorder that is characterized by progressive thinning, steepening, and potential scarring. In the early stages of keratoconus treatment can be modulated with contact lenses but once it reaches to scarring, penetrating keratoplasty (PK) is the standard procedure of care. As there is not enough published data on penetrating keratoplasty in Pakistan and also early visual outcomes post keratoconus keratoplasty have not been established so this study would be beneficial for further research and opting keratoplasty as a procedure for management of advance keratoconus. To determine the frequency of improvement in the visual acuity six months after penetrating keratoplasty in patients of Keratoconus. Methods: Sixty-five eyes of 65 patients fulfilling the inclusion criteria were taken from the Outdoor Clinic of Layton Rahmatulla Benevolent Trust Free Eye and Cancer Hospital. Informed consent was taken and socio-demographic data (name, age, gender, address and contact number) was also recorded. Examination included Visual Acuity with Snellen’s Chart with assessment of light projection in patients with Visual Acuity hand movements or light perception. Slit lamp examination with Haag Streit BQ 900 Slit lamp for assessing the condition of cornea was done. Indirect ophthalmoscopy was performed using 90D lens for fundus examination. B-scan (ocular ultrasonography) with Alcon B-scan was done where fundus examination was not possible. Standard surgical procedure of Penetrating Keratoplasty was carried out on all patients. Visual Acuity was recorded on Day 7, 90 and 180 after the surgery Conclusion: Penetrating Keratoplasty is a safe and reliable procedure for improvement in visual acuity of patients with keratoconus and should be conducted on mass level to avoid blindness caused by keratoconus